Integrated polycaprolactone microsphere-based scaffolds with biomimetic hierarchy and tunable vascularization for osteochondral repair. (15th March 2022) - Gu, Xiang; Zha, Yao; Li, Yawu; Chen, Jia; Liu, Shuaibing; Du, Yingying; Zhang, Shengmin; Wang, Jianglin
Abstract: Osteochondral lesion potentially causes a variety of joint degenerative diseases if it cannot be treated effectively and timely. Microfracture as the conservative surgical choice achieves limited results for the larger defect whereas cartilage patches trigger integrated instability and cartilage fibrosis. To tackle aforementioned issues, here we explore to fabricate an integrated osteochondral scaffold for synergetic regeneration of cartilage and subchondral bone in one system. On the macro level, we fabricated three integrated scaffolds with distinct channel patterns of Non-channel, Consecutive-channel and Inconsecutive-channel via Selective Laser Sintering (SLS). On the micro level, both cartilage zone and subchondral bone zone of integrated scaffold were made of small polycaprolactone (PCL) microspheres and large PCL microspheres, respectively. Our findings showed that Inconsecutive-channel scaffolds possessed integrated hierarchical structure, adaptable compression strength, gradient interconnected porosity. Cartilage zone presented a dense phase for the inhibition of vessel invasion while subchondral bone zone generated a porous phase for the ingrowth of bone and vessel. Both cartilage regeneration and subchondral bone remodeling in the group of Inconsecutive-channel scaffolds have been demonstrated by histological evaluation and immunofluorescence staining in vivo. Consequently, our current work not only achieves an effective and regenerative microsphere scaffold for osteochondral reconstruction, but also provides a feasible methodology to recover injured joint through integrated design with diverse hierarchy. Statement of significance: Recovery of osteochondral lesion highly depends on hierarchical architecture and tunable vascularization in distinct zones. We therefore design a special integrated osteochondral scaffold with inconsecutive channel structure and vascularized modulation. The channel pattern impacts on mechanical strength and the infiltration of bone marrow, and eventually triggers synergetic repair of osteochondral defect. The cartilage zone of integrated scaffolds consisted of small PCL microspheres forms a dense phase for physical restriction of vascularized infiltration whereas the subchondral bone zone made of large PCL microspheres generates porous trabecula-like structure for promoting vascularization. Consequently, the current work indicates both mechanical adaptation and regional vascularized modulation play a pivotal role on osteochondral repair. Graphical abstract: Image, graphical abstract